Helsevesenet trenger vår kompetanse- hvorfor ikke bruke den? En kvalitativ studie av filippinske sykepleieres opplevelse av veien til autorisasjon i Norge - Dahl, Kari; Lohne, Vibeke; Nortvedt, Line (Nordisk tidsskrift for helseforskning, 2019)
The healthcare system need our competence - why not use it? A qualitative study of Filipino nurses experience of their way to accreditation in Norway Healthcare professionals educated outside the EU/EEA are an important source of labor in the Norwegian healthcare system, where nurses and auxiliary nurses from the Philippines constitute the largest group. Complicated authority requirements are attached to accreditation in Norway. The study explores how Filipino nurses with three different approvals in the authorization process, experience the process of accreditation in Norway, using qualitative research interviews. The results show that nurses face challenges related to the authorization process in Norway, which they experience as unworthy, unfair, baffling and economically burdensome, but also with experiences of hope for good prospects. A predictable and a dignified authorization process for Filipino nurses should be developed, so that their knowledge and competence can be included and appreciated in the Norwegian health care services.